sichtbar unsichtbar: Geschlechterwissen in (auto-)biographischen Texten - Schmitt, Mathilde; Kogler, Nina; Schneider, Ursula A.; Heidegger, Maria; Steinsiek, Annette (transcript, 2015)
The self and its gender – what do biographical practices tell us about subjects and identity? To what extent does one determine the other? Analyses of (auto-)biographical gender reflections.